Przedsiębiorczość jako determinanta rozwoju współczesnej organizacji - Malara, Zbigniew (Entrepreneurship as a tool of improving contemporary organization, 2006)
The paper contents important remarks presented in relation to entrepreneurship as a process tightly based upon innovation processes. Its influences into dynamic of contemporary organization was given as well. Some theoretical aspects, e. a definitions and interpretations were presented. Finally, practical advises, useful in creating entrepreneurship process were discussed too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 117-123